A case of ophthalmic neonatorum with disseminated gonococcal dermatitis and gonorrhoea (Bangladesh Journal of Medical Science, 2012)
Ophthalmia neonatorum with disseminated gonococcal dermatitis and gonorrhoea is a rare condition. A neonate of 22 days from a poor socioeconomic condition presented with purulent discharge from eye and vagina and eye for last 18 days and skin lesions for 5 days. The baby as born through vaginal delivery. Gram staining of eye and vaginal discharge revealed gram-negative intracellular diplococcices visualized microscopically inside polymorph nuclear cells. Neonate was diagnosed as a case of ophthalmia neonatorum with disseminated gonococcal dermatitis and gonorrhoea. Neonate was treated with inj. Ceftroaxone 250mg daily intravenously with antibacterial eye drop. On 2nd day, sign symptoms disappear and on 4th day patient was cured. Key words: Ophthalmia neonatum; conorrhoea; disseminated gonococcal dermatitis; HIV. DOI: http://dx.doi.org/10.3329/bjms.v10i4.9507 BJMS 2011; 10(4): 299-301